2009
DOI: 10.1093/ntr/ntp041
|View full text |Cite
|
Sign up to set email alerts
|

A prospective examination of distress tolerance and early smoking lapse in adult self-quitters

Abstract: Auditory Serial Addition Test (a psychological challenge task) was not a signifi cant predictor of earlier smoking lapse.Discussion: These results are discussed in relation to refi ning theoretical models of the role of distress tolerance in early smoking lapse and the utility of such models in the development of specialized treatment approaches for smoking cessation. IntroductionAn increased level of theoretical and empirical attention has focused on better understanding the nature of early smoking lapse in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
168
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 151 publications
(180 citation statements)
references
References 48 publications
6
168
1
5
Order By: Relevance
“…Thus, tolerance of the CO 2 -enriched air challenge may not reflect latent individual differences shared by tolerance of the breath-holding and mirror-tracing tasks. The latter effect was unexpected, and is theoretically interesting, in light of the fact that breath-holding and CO 2 -enriched air challenge persistence are conceptually thought to reflect common or related individual differences in tolerance of physiological anxious arousal (Brown et al, 2009). It is possible a higher-order latent variable related to individual differences in behavioral tolerance of various forms of distress (e.g., physiological anxious arousal and psychological frustration) may, in part, account for strong covariation between performance on these tasks.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, tolerance of the CO 2 -enriched air challenge may not reflect latent individual differences shared by tolerance of the breath-holding and mirror-tracing tasks. The latter effect was unexpected, and is theoretically interesting, in light of the fact that breath-holding and CO 2 -enriched air challenge persistence are conceptually thought to reflect common or related individual differences in tolerance of physiological anxious arousal (Brown et al, 2009). It is possible a higher-order latent variable related to individual differences in behavioral tolerance of various forms of distress (e.g., physiological anxious arousal and psychological frustration) may, in part, account for strong covariation between performance on these tasks.…”
Section: Discussionmentioning
confidence: 96%
“…Breath-holding duration is time to exhalation. This task has frequently been used as measure of physical distress intolerance (Brown et al, 2009;Hajek et al, 1987), with shorter durations of breath-holding indicating greater intolerance of physical distress. Research has suggested that breath-holding duration maintains unique predictive value beyond the effects of physical health conditions, active substance use, and anxiety sensitivity (Hogan et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…A 1 -week time frame was chosen to capture the initial volatile period during which most smoking lapses occur ( Brown et al, 2009 ;Garvey, Bliss, Hitchcock, Heinold, & Rosner, 1992 ) and to minimize the burden of daily laboratory assessments. Incentive amounts were selected to maximize intersubject variability in order to examine predictors of outcomes within the model.…”
Section: Introductionmentioning
confidence: 99%